Assessing of the forensic reports documented by forensic medicine polyclinic of Adiyaman education and research hospital in 2017-2018 (Annals of Medical Research, 2021)
Aim: Blunt trauma, firearm/sharp object injuries, suicide, and accident are judicial events that can cause injury or death of individuals are considered. They are the duties of physicians to examine forensic cases in a timely and carefully manner and to prepare reports by recording the findings obtained. In this study, it was aimed to examine the characteristics of the reports prepared in the polyclinic and thus to determine the forensic case data in our region.Materials and Methods: In this study, 1,222 cases who lived in and around the province of Adıyaman and whose forensic reports wereprepared due to physical injury were retrospectively in 2017 and 2018. We retrospectively examined in terms of sociodemographic characteristics, report date, referring judicial authority, cause of the event, injury site and the decisions.Results: 930 (76.1%) of all cases were male and 292 (23.9%) were female. It was observed that the reports were prepared most commonly because of battery (46.8%), followed by a traffic accident (29.5%). It was found that injuries occurred most commonly in the head - neck region (n = 355; 29.1%) and the extremity region is secondly (n = 298 ; 24.4%). Nasal bone was the most commonly broken bone (n = 87; 18.2%).Conclusion: It was thought that determining regional profiles and data in judicial events would contribute to taking preventive measures (education-psychosocial support etc.) and appropriate planning. In addition, preventive measures should be taken for accidental events that occur in childhood and old age.